Humans Conform to Robots: Disambiguating Trust, Truth, and Conformity - Salomons, Nicole; van der Linden, Michael; Strohkorb Sebo, Sarah; Scassellati, Brian (2018 13th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2018)
Asch's [2] conformity experiment has shown that people are prone to adjusting their view to match those of group members even when they believe the answer of the group to be wrong. Previous studies have attempted to replicate Asch's experiment with a group of robots but have failed to observe conformity [7, 25]. One explanation can be made using Hodges and Geyers work [17], in which they propose that people consider distinct criteria (truth, trust, and social solidarity) when deciding whether to conform to others. In order to study how trust and truth affect conformity, we propose an experiment in which participants play a game with three robots, in which there are no objective answers. We measured how many times participants changed their preliminary answers to match the group of robots' in their final answer. We conducted a between-subjects study (N = 30) in which there were two conditions: one in which participants saw the group of robots' preliminary answer before deciding their final answer, and a control condition in which they did not know the robots' preliminary answer. Participants in the experimental condition conformed significantly more (29%) than participants in the control condition (6%). Therefore we have shown that groups of robots can cause people to conform to them. Additionally trust plays a role in conformity: initially, participants conformed to robots at a similar rate to Asch's participants, however, many participants stop conforming later in the game when trust is lost due to the robots choosing an incorrect answer.